2014
DOI: 10.3109/03014460.2014.897755
|View full text |Cite
|
Sign up to set email alerts
|

Body fatness in relation to physical activity and selected socioeconomic parameters of adolescents aged 15–17 years in Merida, Yucatan

Abstract: Adolescents with excess weight (overweight + obesity) reported being less physically active. SES and PA were strongly related to growth and body fatness in the studied adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…This corresponds to differential rates of stunting as reported previously in the same population. 28,29 In a subsample of 283 adolescents (127 boys and 156 girls) aged 12 to 16 years, drawn from the same database, frequency of stunting again was higher among girls (14.74%) than boys (6.3%). 28 A similar trend was observed in another subsample from the same database.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This corresponds to differential rates of stunting as reported previously in the same population. 28,29 In a subsample of 283 adolescents (127 boys and 156 girls) aged 12 to 16 years, drawn from the same database, frequency of stunting again was higher among girls (14.74%) than boys (6.3%). 28 A similar trend was observed in another subsample from the same database.…”
Section: Discussionmentioning
confidence: 98%
“…For the present study, we used a purposive nonprobability sample 38 that was not representative of the city of Merida and was both ethnically and socioeconomically heterogeneous as reported earlier. 28,29 Participants’ ethnic background was defined as either Maya or Mestizo (a mix of Maya, other Mexican, and/or European ancestry). In Mexico, people use 2 surnames, the first is the father’s first surname and the second is the mother’s first surname.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently low mean height values (<148 cm) have been reported for adult Maya women in Merida (Azcorra et al, ; Varela‐Silva et al, ), largely due to chronic adverse living conditions. Yucatan, particularly Merida, has also strikingly high rates of overweight and obesity among children and adults (Azcorra, Dickinson, & Rothenberg, ; Azcorra et al, ; Datta Banik, Andrade Olalde, Rodriguez, & Dickinson, ; Datta Banik, Castillo, Rodriguez, & Dickinson, ; Mendez et al, ; Varela‐Silva et al, ; Wilson et al, ). A recent National Survey of Health and Nutrition in Mexico (INSP, ) found that children 5‐ to 11‐years‐of‐age in Yucatan had a 22% risk for overweight (>+1 standard deviation or SD and ≤ +2 SD of BMI‐for‐age), and 23% for obesity (>+2 SD of BMI‐for‐age).…”
Section: Participants and Methodsmentioning
confidence: 99%
“…26,27 Accelerometry data show that girls have higher PA levels than boys, 28 while self-reported data show that boys have higher PA levels than girls, 29 and almost double the energy expenditure. 30 This grade was decreased from C+ to C reflecting the fact that available national estimates have not been updated, that gender differences exist, and individual study data show that Mexican children and youth engage in PA levels that are below the recommended levels.…”
Section: Overall Physical Activity Level: C (6)mentioning
confidence: 99%